Part of the global DOC versus AOU (dissolved organic carbon/apparent oxygen utilization) data compilation, Arabian Sea - Hansell, Dennis A; Peltzer, Edward T (PANGAEA, 1998)
Concentrations of total organic carbon (TOC) were determined on samples collected during six cruises in the northern Arabian Sea during the 1995 US JGOFS Arabian Sea Process Study. Total organic carbon concentrations and integrated stocks in the upper ocean varied both spatially and seasonally. Highest mixed-layer TOC concentrations (80-100 µM C) were observed near the coast when upwelling was not active, while upwelling tended to reduce local concentrations. In the open ocean, highest mixed-layer TOC concentrations (80-95 µM C) developed in winter (period of the NE Monsoon) and remained through mid summer (early to mid-SW Monsoon). Lowest open ocean mixed-layer concentrations (65-75 µM C) occurred late in the summer (late SW Monsoon) and during the Fall Intermonsoon period. The changes in TOC concentrations resulted in seasonal variations in mean TOC stocks (upper 150 m) of 1.5-2 mole C/m**2, with the lowest stocks found late in the summer during the SW Monsoon-Fall Intermonsoon transition. The seasonal accumulation of TOC north of 15°N was 31-41 x 10**12 g C, mostly taking place over the period of the NE Monsoon, and equivalent to 6-8% of annual primary production estimated for that region in the mid-1970s. A net TOC production rate of 12 mmole C/m**2/d over the period of the NE Monsoon represented ~80% of net community production. Net TOC production was nil during the SW Monsoon, so vertical export would have dominated the export terms over that period. Total organic carbon concentrations varied in vertical profiles with the vertical layering of the water masses, with the Persian Gulf Water TOC concentrations showing a clear signal. Deep water (>2000 m) TOC concentrations were uniform across the basin and over the period of the cruises, averaging 42.3±1.4 µM C.
Supplement to: Hansell, Dennis A; Peltzer, Edward T (1998): Spatial and temporal variations of total organic carbon in the Arabian sea. Deep Sea Research Part II: Topical Studies in Oceanography, 45(10-11), 2171-2193
Keywords: Joint Global Ocean Flux Study (JGOFS)